Understanding bubble growth process under decompression and its effects on the flotation phenomena. (1st January 2020) - Wang, Yunfan; Pan, Zuchao; Jiao, Fen; Qin, Wenqing
Highlights: Relationship between dissolved oxygen and vacuum pressure was studied. Nanobubbles were imaged on the surface of calcite. The growth kinetics of microbubbles under decompression were studied. Decompression flotation can reduce the necessity of frother addition. Decompression flotation has a significant effect on increasing mineral recovery. Abstract: The aim of this study is to explore the effect of dissolved oxygen difference (DOD) on the formation of micro-nanobubbles and flotation systems. The nanobubbles on the calcite surface generated by the method of "Deep degassing water - saturated dissolved gas water exchange" were imaged by atomic force microscopy (AFM). Then, under decompression conditions, the micron-sized bubbles on the calcite surface were observed by a microscope digital camera. It was found that the growth rate of the micron-sized bubbles obeys the gas evolution rate equation under classical mechanics, which confirmed that the DOD under vacuum/decompression conditions is the decisive factor leading to the generation of micro-nanobubbles. At the same time, through a homemade vacuum Hallimond tube, the effects of the instantaneous gas evolution rate and the total amount of gas evolution on the single mineral flotation of calcite were investigated under a vacuum pressure of −50 KPa and a vacuum pressure of −70 KPa (The absolute pressure was 51 KPa and 31 KPa). The test results confirmed that if only the gas evolution rate is different, the recovery of calcite at a vacuum pressure of −70 KPa is 8.5% higher than that at a vacuum pressure of −50 KPa. However, if the gas evolution rate and total amount of gas evolution are simultaneously changed, the recovery of calcite at a vacuum pressure of −70 KPa is 12.31% higher than that at a vacuum pressure of −50 KPa. This result indicates that the formation rate and total amount of micro-nanobubbles have an important influence on flotation. At the same time, the proposal of DOD and the dynamic analysis of micro-nanobubble are good predictors for dissolved air flotation (including decompression flotation).